Shallow crustal composition of Mercury as revealed by spectral properties and geological units of two impact craters. (15th December 2015) - D'Incecco, Piero; Helbert, Jörn; D'Amore, Mario; Maturilli, Alessandro; Head, James W.; Klima, Rachel L.; Izenberg, Noam R.; McClintock, William E.; Hiesinger, Harald; Ferrari, Sabrina
Abstract: We have performed a combined geological and spectral analysis of two impact craters on Mercury: the 15 km diameter Waters crater (106°W; 9°S) and the 62.3 km diameter Kuiper crater (30°W; 11°S). Using the Mercury Dual Imaging System (MDIS) Narrow Angle Camera (NAC) dataset we defined and mapped several units for each crater and for an external reference area far from any impact related deposits. For each of these units we extracted all spectra from the MESSENGER Atmosphere and Surface Composition Spectrometer (MASCS) Visible-InfraRed Spectrograph (VIRS) applying a first order photometric correction. For all the mapped units, we analyzed the spectral slope in two wavelength ranges, 350–450 nm and 450–650 nm, and the absolute reflectance in the 700–750 nm range. Normalized spectra of Waters crater display a generally bluer spectral slope than the external reference area over both wavelength windows. Normalized spectra of Kuiper crater generally display a redder slope than the external reference area in the 350–450 nm window, while they display a bluer slope than the external reference area in the 450–650 nm wavelength range. The combined use of geological and spectral analyses enables reconstruction of the local scale stratigraphy beneath the two craters, providing insight into the properties of the shallower crust of Mercury. Kuiper crater, being ~4 times larger than Waters crater, exposes deeper layers with distinctive composition, while the result for Waters crater might indicate substantial compositional homogeneity with the surrounding intercrater plains, though we cannot exclude the occurrence of horizontal compositional heterogeneities in the shallow sub-surface. Highlights: We look for the presence vertical variations in the crustal composition of Mercury. We perform a geologically supervised classification across Kuiper and Waters craters. We reconstruct pre-impact stratigraphy beneath the two impact craters. Waters crater׳s units formed within the layer of origin of intercrater plains. Kuiper crater׳s units originated from a deeper layer with distinct composition. The results confirm the presence of vertical heterogeneities in the crust of Mercury.